LINGUISTIC PERSPECTIVES ON ENGLISH TEACHERS’ PERCEPTIONS OF CULTURALLY RESPONSIVE TEACHING - Ani Ayu Sariningsih; Hepy Adityarini (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
Culturally Responsive Teaching (CRT) has been recognized as an effective pedagogical approach that integrates students’ cultural backgrounds into the learning process, yet limited research in Indonesia has examined English teachers’ perceptions of CRT through a linguistic lens. This study explores how junior high school English teachers in Klaten perceive and discursively construct CRT in their classrooms. Employing a qualitative design, data were collected through semi-structured interviews with six English teachers of diverse backgrounds, and analyzed using Miles and Huberman’s interactive model, focusing both on thematic content and linguistic markers such as lexical choices, metaphors, and stance-taking. The findings reveal three patterns of teachers’ understanding: some framed CRT as a teaching method, others as a broader educational approach, while one admitted unfamiliarity with the concept. These perceptions were linguistically constructed through markers of uncertainty (e.g., interrogatives, hedges), evaluative and metaphorical language (e.g., “learning asset”), and stance-taking devices that reflected confidence or hesitation. In implementation, teachers integrated CRT through project-based learning, local cultural narratives, and school routines, though coherence varied depending on their conceptual grounding. Obstacles included limited teacher competence, insufficient facilities, students’ cultural identity resistance to English, and low self-confidence, while strategies involved professional development, use of technology, relationship building, and material adaptation. The study concludes that teachers’ discourse both reflects and shapes their engagement with CRT, and that without strong theoretical foundations, practices risk remaining intuitive rather than systematic. It recommends strengthening professional development programs to combine theoretical understanding and practical strategies, thereby supporting more inclusive and culturally grounded English language teaching in Indonesia.